1995
DOI: 10.1038/sc.1995.146
|View full text |Cite
|
Sign up to set email alerts
|

Collagen injections for intrinsic sphincter deficiency in the neuropathic urethra

Abstract: Twelve subjects experiencing stress urinary incontinence caused by spinal injury or myelomeningocele were treated by periurethral injection of a bulking agent, glutaraldehyde cross-linked (GAX) collagen. Of the 11 subjects who completed the program, seven were either cured or improved and four were only slightly improved or no better following injection. The valsalva (abdominal) leak point pressure (LPP) rose an average of 57 cm H20 (pre-treatment mean of 60 cm H20 versus post-treatment mean of 117 cm H20) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Aside from PPI, BA use had also been reported in male neuropathic and pediatric populations . Furthermore, it had been proven that prior BA injections do not affect outcomes of subsequent surgical interventions should the need arise …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from PPI, BA use had also been reported in male neuropathic and pediatric populations . Furthermore, it had been proven that prior BA injections do not affect outcomes of subsequent surgical interventions should the need arise …”
Section: Resultsmentioning
confidence: 99%
“…Aside from PPI, BA use had also been reported in male neuropathic and pediatric populations. 42,44,48 Furthermore, it had been proven that prior BA injections do not affect outcomes of subsequent surgical interventions should the need arise. 49 Even though BA use had decreased over the last decade because of its lack of efficacy and reliability and advances in slings, a study reported urethral BA injections "remain the exclusive incontinence procedure for PPI performed by 49% of US urologists" as of 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of collagen has also been described specifically for patients with neurogenic bladder. Bennett et al [25] cited an improvement or cure in seven of 11 patients who received collagen injections, and Tabibian and Ginsberg [26] noted an improvement in six of nine men treated. Although the fact that these patients have often not had prior therapy and the fibrotic reaction allow for an easier injection and better response, the need for regular intermittent catheterization in this younger population would result in the need for multiple injections over the patient's lifetime to maintain effect.…”
Section: Management Of An Incompetent Outletmentioning
confidence: 97%
“…The least invasive of these are bulking agents, but their success rates are in the region of 20%–50% 20. The artificial urinary sphincter has the highest success rate of around 70%, although the procedure suffers from the complications listed for a foreign body implant and requires revision after a number of years 21…”
Section: Current and Emerging Therapiesmentioning
confidence: 99%